Anti-interferon-γ autoantibodies syndrome and opportunistic infections: systematic literature review - Chen, Ni; Hong, Limei; Liang, Hanlin; Yu, Qingliang; Liang, Siqiao; He, Zhiyi (Frontiers in Immunology, 2025)
IntroductionAnti-interferon-γ autoantibodies (AIGAs) syndrome is a rare, adult-onset immunodeficiency characterized by increased susceptibility to various opportunistic infections. Currently, there are no standardized diagnostic or therapeutic guidelines for AIGAs syndrome, making clinical management challenging.GoalsTo summarize and synthesize the published literature on the demographic characteristics, infection types, affected organs, treatments, and outcomes of AIGAs syndrome. This review aims to provide a comprehensive summary of current knowledge regarding the epidemiology, pathogenesis, clinical manifestations, diagnosis, and treatment of AIGAs syndrome.MethodsWe searched PubMed, EMBASE for publications in English between January 1, 2004, and March 8, 2025 relating to AIGAs syndrome. Data from eligible studies were extracted and synthesized to summarize demographic characteristics, infection types, affected organs, treatments, and outcomes.ResultsA total of 149 eligible studies, encompassing 1430 patients (664 males [46.43%], 672 females [46.99%], and 94 with unmentioned gender), were included. Patients frequently presented with two or more opportunistic infections, most commonly non-tuberculous mycobacteria (NTM, 55.69%), Talaromyces marneffei (TM, 26.98%), Salmonella spp. (12.43%), Mycobacterium tuberculosis (9.34%), and varicella-zoster virus (VZV, 9.57%). Multi-organ involvement was common, particularly affecting lymph nodes (70.24%), lungs (58.75%), bones/joints (38.89%), and skin (45.16%). Clinical outcomes included remission (45.08%), persistent (15.98%), relapse (21.62%), and death (11.68%). In addition to anti-infective therapy, corticosteroids, rituximab, and cyclophosphamide were commonly employed as immunotherapies.ConclusionsAIGAs syndrome is associated with diverse opportunistic infections, particularly NTM, TM, Salmonella, Mycobacterium tuberculosis, and VZV. Multi-organ and multi-system involvement is frequent, with a tendency toward persistent or relapsing disease and associated mortality. Corticosteroids may represent the most promising immunomodulatory therapy in the future.